2010
DOI: 10.1007/s12011-010-8765-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In-Feed Inclusion of Clinoptilolite on Blood Serum Concentrations of Aluminium and Inorganic Phosphorus and on Ruminal Ph and Volatile Fatty Acid Concentrations in Dairy Cows

Abstract: The experiment investigated the effects of the dietary inclusion of 200 g of the natural zeolite, clinoptilolite on the blood serum concentrations of aluminium (Al) and inorganic phosphorus (P) as well as on the ruminal pH and the ruminal concentrations of Al and P and of certain volatile fatty acids. Sixteen Holstein cows with a rumen fistula were randomly assigned to one of two groups. Group A cows (n = 8) were fed the basal ration supplemented with 200 g of clinoptilolite per day, and group B cows (n = 8) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
3
9
0
1
Order By: Relevance
“…The relative content of dry matter in colostrum of treated group was higher in 2nd colostrum, with relatively higher content of total protein and fat. Considering that colostrum fat is primarily derived from the free fatty acids absorbed in the rumen, the results showed increasing percentage of fat in the colostrum of clinoptilolite supplemented (C150) group, are comparable to the results of Karatzia et al (2011) who reported an increase in the acetate concentration in cows supplemented with zeolite. In the study by Khachlouf et al (2018) the addition of zeolite also resulted in the highest rumen molar percentage of acetate and higher acetate: propionate ratio.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The relative content of dry matter in colostrum of treated group was higher in 2nd colostrum, with relatively higher content of total protein and fat. Considering that colostrum fat is primarily derived from the free fatty acids absorbed in the rumen, the results showed increasing percentage of fat in the colostrum of clinoptilolite supplemented (C150) group, are comparable to the results of Karatzia et al (2011) who reported an increase in the acetate concentration in cows supplemented with zeolite. In the study by Khachlouf et al (2018) the addition of zeolite also resulted in the highest rumen molar percentage of acetate and higher acetate: propionate ratio.…”
Section: Discussionsupporting
confidence: 80%
“…Considering that colostrum fat is primarily derived from the free fatty acids absorbed in the rumen, the results showed increasing percentage of fat in the colostrum of clinoptilolite supplemented (C150) group, are comparable to the results of Karatzia et al . (2011) who reported an increase in the acetate concentration in cows supplemented with zeolite. In the study by Khachlouf et al .…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of clinoptilolite tended to decrease daily gain and to increase feed to gain ratio. Karatzia et al (2011) administered 200 g clinoptilolite per head per day (corresponding to approximately 15 000 mg clinoptilolite/kg feed dry matter) to a group of eight rumen-fistulated Holstein cows, another eight cows remaining untreated. During the observation period of 12 weeks, clinoptilolite feeding resulted in an increase in ruminal pH and acetate in the ruminal fluid and a decrease in propionate.…”
Section: Safety For the Target Speciesmentioning
confidence: 99%
“…Dietary supplementation with zeolite clay exhibited positive effects on nutrients digestion and growth performance of sheep [ 9 ]. Furthermore, zeolite positively affected animal health status and performance due to its characteristic sorbent properties that modify the ruminal environment [ 10 , 11 ]. Nanoclays and other nano-particles have been shown to specifically absorb mycotoxins through the gastrointestinal tract of ruminants [ 12 ].…”
Section: Introductionmentioning
confidence: 99%